2020
DOI: 10.1007/s12161-020-01863-8
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatography Determination of Free Sugars and Mannitol in Mushrooms Using Corona Charged Aerosol Detection

Abstract: Refractive index detector is usually used in the analysis of sugars in mushrooms, which is characterized by poor sensitivity, reproducibility, and susceptibility to interference from co-eluting sample components. In the current study, identification and determination of free sugars in mushroom samples by high-performance liquid chromatography coupled to corona charged aerosol detector (HPLC-CAD) were presented for the first time. The best chromatographic separation was performed on a Shodex Asahipak NH2P-50 4E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
2
14
1
1
Order By: Relevance
“…The glucose yield of 1.582mg/mL reported in the present study is within the range of glucose content of Pleurotus species previously reported [34,35]. The hydrolysis of mushroom biomass was attributed to the ability of the crude extract to display adequate balance between the activities of β-glucosidase, FPase, and cellobiohydrolase which are key in mushroom cell-wall degradation [36][37].…”
Section: Model Validationsupporting
confidence: 81%
“…The glucose yield of 1.582mg/mL reported in the present study is within the range of glucose content of Pleurotus species previously reported [34,35]. The hydrolysis of mushroom biomass was attributed to the ability of the crude extract to display adequate balance between the activities of β-glucosidase, FPase, and cellobiohydrolase which are key in mushroom cell-wall degradation [36][37].…”
Section: Model Validationsupporting
confidence: 81%
“…The reported glucose yield (1.639 ±0.04 mg mL −1 ) in the present study is above glucose yields obtained from Pleurotus species previously reported (Sławińska et al 2020, Zhou et al 2912). This could have resulted from the e cient hydrolysis of mushroom biomass and the presence of adequate balance between different enzymes in the crude extract.…”
Section: Discussionsupporting
confidence: 70%
“…Most state-of-the-art methods use well-accepted analytical instruments to selectively determine a single carbohydrate or multiple carbohydrates (i.e., sugar profile methods that generally include two or more of the most common mono- and disaccharides—glucose, fructose, galactose, lactose, sucrose, and maltose) in ingredients and finished (food) products. Specifically, chromatographic methods like high-performance anion-exchange chromatography with pulsed amperometric (HPAEC–PAD; 37 , 38 ) or mass spectrometric detection (HPAEC–MS; 39 ), and HPLC with tandem mass spectrometric (HPLC–MS/MS; 40 ), evaporative light-scattering (HPLC–ELS; 41 ), refractive index (HPLC–RI; 42 ), or charged aerosol detection (HPLC–CAD; 43 , 44 ) have been used. These techniques continue to be developed and optimized to extend their applicability to various complex food matrixes while providing good accuracy and precision, high sensitivity and resolution, and required LOD and LOQ.…”
Section: Analytical Methods For Quantitating Sweet-tasting Moleculesmentioning
confidence: 99%